Relationship between the richness of tree species and edaphoclimatic characteristics of the south region of Bahia, Brazil. (16th August 2022) - Teles, Carolina Barreto; Magnago, Luiz Fernando Silva; Carilo Filho, Leildo Machado; Piotto, Daniel
ABSTRACT: The regions between the tropics provide climatic characteristics that contribute to the formation of unique vegetation typologies, the Tropical Forests. It is estimated that these forests are home to about 50 000 tree species. The Atlantic Forest, located mostly on the Brazilian coast is an example of the richness of phanerophytes inside an important hotspot for biodiversity. Understanding the relationship between these edaphoclimatic factors and the richness of tree species in the Atlantic Forest is important to establish conservation strategies in this threatened biome. Our main objective was to analyse the relationship between abiotic variables and tree species richness in the southern region of the state of Bahia, Brazil. In this sense, we used data from tree species and abiotic factors (extracted from the WorldClim and FAO platforms) in a selection of mixed generalized linear multimodels. Variables related to temperature and precipitation in the driest periods influenced the richness of tree species in the study region. Whereas temperature seasonality and minimum temperature of the coldest month influenced negatively the values for extrapolated richness the maximum temperature of the hottest month exhibited a positive influence for richness indexes. These results emphasize that the maintenance of the arboreal richness in tropical zones is directly dependent of the climatic seasonality. In the present study, we point out the importance of climatic factors for the maintenance of tree species in a region that has expressive numbers of tree species per hectare, one of the world records in this index.